2017
DOI: 10.2147/cia.s141905
|View full text |Cite
|
Sign up to set email alerts
|

Assessing capacity to consent for research in cognitively impaired older patients

Abstract: BackgroundThe number of clinical trials including older patients, and particularly patients with cognitive impairment, is increasing. While statutory provisions exist to make sure that the capacity to consent is assessed systematically for each patient, many gray areas remain with regard to how this assessment is made or should be made in the routine practice of clinical research.ObjectivesThe aim of this review was to draw up an inventory of assessment tools evaluating older patients’ capacity to consent spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 84 publications
0
76
0
Order By: Relevance
“…Testing of the DMC is used to determine the extent of an individual's independence 13 . Therefore, making judgments based on only one parameter would be erroneous 13 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Testing of the DMC is used to determine the extent of an individual's independence 13 . Therefore, making judgments based on only one parameter would be erroneous 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Testing of the DMC is used to determine the extent of an individual's independence 13 . Therefore, making judgments based on only one parameter would be erroneous 13 . However, ndings showed that the Geriatrician relied only on one method while testing the DMC, either a tool or clinical experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient needs to be able to express a treatment choice, and this decision needs to be stable enough for the treat- The use of structured approaches to assess these abilities can be very helpful for termined cutoff separating capacity and incapacity and appears difficult to use and time-consuming [11] . istics [4] .…”
Section: Communication/expressing a Choicementioning
confidence: 99%